1979
DOI: 10.1126/science.206.4422.1043
|View full text |Cite
|
Sign up to set email alerts
|

Ecology and Acculturation Among Native Peoples of Central Brazil

Abstract: Simple exposure to Western goods may not be a sufficient explanation of why isolated village communities increase their participation in external market economies. The degree of market participation by four native villages in central Brazil is related to the difficulty of making a living from slash-and-burn subsistence agriculture as measured by the ratio of labor input to food output.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0
9

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(60 citation statements)
references
References 15 publications
1
50
0
9
Order By: Relevance
“…Even though the outcome for these communities is still unclear, history has shown that the caiçaras are relatively flexible when it comes to adapting to different economic and social cycles (A. Begossi, unpublished manuscript), but this can be limited to how their resilience is affected. The results presented here seem to reinforce the point of view of Gross et al (1979), who note that, the harder it is for the inhabitants of a community to make a living through traditional means, the greater the extent of their market participation. Wherever communities are undergoing similar processes, market participation seems to be related to the restrictions imposed on the use of local resources or to a reduction in available resources, usually caused by external factors.…”
Section: Discussionsupporting
confidence: 87%
“…Even though the outcome for these communities is still unclear, history has shown that the caiçaras are relatively flexible when it comes to adapting to different economic and social cycles (A. Begossi, unpublished manuscript), but this can be limited to how their resilience is affected. The results presented here seem to reinforce the point of view of Gross et al (1979), who note that, the harder it is for the inhabitants of a community to make a living through traditional means, the greater the extent of their market participation. Wherever communities are undergoing similar processes, market participation seems to be related to the restrictions imposed on the use of local resources or to a reduction in available resources, usually caused by external factors.…”
Section: Discussionsupporting
confidence: 87%
“…In Brazil, however, the issue of LEK transformations has not yet been addressed despite the significant economic and socio-cultural changes that its rural/local populations have experienced; which include native peoples (GROSS et al, 1979;FORLINE 1997;COIMBRA JR. et al, 2002;PRADO et al, 2012), caboclos (MURRIETA 1998(MURRIETA ,2001BRONDIZIO, 2008;ADAMS et al, 2009), caiçaras (ADAMS, 2000;HANAZAKI and BEGOSSI, 2003;SANCHES, 2004) and quilombolas (PENNA-FIRME and BRONDIZIO, 2007;PENNA-FIRME, 2012;ADAMS et al, 2013).…”
Section: Theoretical Landmarks and Central Debates In Ethnobiologymentioning
confidence: 99%
“…Tais mudanças repercutem diretamente sobre os hábitos alimentares e o estado nutricional desses grupos, principalmente durante o processo inicial de inserção na economia de mercado regional (cf. Coimbra Jr., 1989;Flowers, 1983;Gross et al, 1979). Em decorrên-cia disso, atividades básicas de subsistência tendem a ser parcial ou totalmente abandonadas, levando à redução na variabilidade alimentar e maior dependência em produtos industrializados.…”
Section: Introductionunclassified